Residential Equilibrium in a Multifractal Metropolitan Area. - Isabelle Thomas; Jean Cavailhes; Pierre Frankhauser; Dominique Peeters (European Regional Science Association (ERSA), 2006)
In this paper, an urban economic model of residential location is combined with multifractal geometry (Sierpinski carpet) in order to model and analyse the spatial structure of a metropolitan area. This area is made of an urban system organised hierarchically around a central CBD, as well as of green spaces that have an inverse hierarchical organisation. The properties of the model are studied by means of analytical solutions. Then, simulation are made, which are based of French urban realities. This enables one to choose realistic parameters and to analyse the effects of several modelling assumptions (changes in preferences, economic shocks, …). The modelling results show that French periurbanisation of the last 30 years can be explained by the increase in income and by the decrease in transportation costs, probably without any changes in households preferences.
Keywords: 330